Influence of fly ash blending on hydration and physical behavior of Belite-Alite-Ye'elimite cements - Londono-Zuluaga, Diana; Tobón, Jorge Iván; García-Aranda, Miguel Ángel; Santacruz-Cruz, María Isabel; Gómez-de-la-Torre, María de los Ángeles (My University, 2018)
A cement powder, composed of belite, alite and ye’elimite, was blended with 0, 15 and 30 wt% of fly ash and the resulting lended cements were further characterized. During hydration, the presence of fly ash caused the partial inhibition of both AFt degradation and belite reactivity, even after 180 days. The compressive strength of the corresponding mortars increased by increasing the fly ash content (68, 73 and 82 MPa for mortars with 0, 15 and 30 wt% of fly ash, respectively, at 180 curing days), mainly due to the diminishing porosity and pore size values. Although pozzolanic reaction has not been directly proved there are indirect evidences.
Keywords: Cemento; Cenizas volantes; Belite–alite–ye’elimite cement; Fly ash; Hydration; Rietveld method; Phase evolution; NMR